2010
DOI: 10.1007/s00592-010-0233-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperlipidemias in children: effect of plant sterol supplementation on plasma lipids and markers of cholesterol synthesis and absorption

Abstract: Plant sterols lower serum cholesterol concentration. Available data have confirmed the lipid-lowering efficacy in adults, while there is a relative dearth of data in children and almost exclusively restricted to subjects with familial hypercholesterolemia (FH). Aim of the present study was to evaluate the efficacy, tolerability and safety of plant sterol supplementation in children with different forms of primary hyperlipidemias. The effect of plant sterol consumption on plasma lipids was evaluated in 32 child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 31 publications
2
28
0
3
Order By: Relevance
“…As many studies (Casas-Agustench et al, 2012;Demonty et al, 2006;Garaiova et al, 2013;Gonç alves et al, 2006;Guardamagna et al, 2011;Maki et al, 2012;Pá rraga et al, 2011;Weingä rtner et al, 2009;Zhao et al, 2011) have already indicated, plant sterols are able to actively influence lipid profile. The mean LDL-cholesterol reduction after consumption of plant sterol-supplemented foods ranges from 5.9% to 10.4% (Casas-Agustench et al, 2012).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…As many studies (Casas-Agustench et al, 2012;Demonty et al, 2006;Garaiova et al, 2013;Gonç alves et al, 2006;Guardamagna et al, 2011;Maki et al, 2012;Pá rraga et al, 2011;Weingä rtner et al, 2009;Zhao et al, 2011) have already indicated, plant sterols are able to actively influence lipid profile. The mean LDL-cholesterol reduction after consumption of plant sterol-supplemented foods ranges from 5.9% to 10.4% (Casas-Agustench et al, 2012).…”
mentioning
confidence: 97%
“…Many studies have evaluated the potential role of nutraceuticals in the prevention of dyslipidaemia both in animal models (Alshatwi et al, 2011;Chen et al, 2008;Dvir et al, 2009;Huang & Lin, 2012a, 2012b and in humans (Becker et al, 2009;CasasAgustench et al, 2012;Demonty et al, 2006;Dulin et al, 2006;Garaiova et al, 2013;Gonç alves et al, 2006;Guardamagna et al, 2011;Izzo et al, 2010;Maki et al, 2012;Marazzi et al, 2011;Pá rraga et al, 2011;Qin et al, 2009;Rayman et al, 2011;Sirtori et al, 2009;Tomé -Carneiro et al, 2012;Weingä rtner, Bö hm, & Laufs, 2009;Wofford et al, 2012;Wong et al, 2010;Zhao et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, this trend in impairment was found in Zucker diabetic rats [101] and in type 2 diabetic subjects [71]. Plant sterols and stanols have been effectively shown to lower plasma cholesterol levels in familial hypercholesterolemia patients through ABCG5/G8 transporters [102]. Use of these sterols and stanols as cholesterollowering agents and as biomarkers of cardiovascular disease have been reviewed [103] [104].…”
Section: Pharmacological Targeting Of Intestinal Cholesterol Absorptionmentioning
confidence: 85%
“…Suplementos: Los fitoesteroles o fitoestanoles son esteroles de origen vegetal (maíz, soya, maravilla, canola, nueces y cereales) que ayudan a reducir el c-ldl sin efectos adversos en niños 17,30,31 . actúan en el intestino mediante 3 mecanismos: inhiben la absorción del colesterol dietario y biliar, la re-esterificación de los ácidos grasos y estimulan la actividad y expresión del transportador que secreta el colesterol desde los enterocitos hacia el lumen.…”
Section: Tratamiento No Farmacológicounclassified